Pregnancy Outcomes of Women With Polycystic Ovary Syndrome for the First In Vitro Fertilization Treatment: A Retrospective Cohort Study With 7678 Patients - Liu, Su; Mo, Meilan; Xiao, Shan; Li, Longfei; Hu, Xiuyu; Hong, Ling; Wang, Linlin; Lian, Ruochun; Huang, Chunyu; Zeng, Yong; Diao, Lianghui (Frontiers in Endocrinology, 2020)
ABSTRACT Background: The risk of adverse pregnancy outcomes is increased by having a polycystic ovary syndrome (PCOS) diagnosis. However, the confounders in previous studies preclude firm conclusions, and further studies are warranted. Objectives: To investigate whether PCOS affects pregnancy outcomes and complications in infertile women undergoing their first in vitro fertilization (IVF) treatment, taking into account important confounders. Methods: We performed a retrospective cohort study of 7678 infertile women, including 666 women with PCOS and 7012 controls undergoing their first IVF treatment at a private fertility center from January 2010 to December 2017. Our main outcome was the impact of PCOS on adverse pregnancy outcomes (miscarriage, preterm delivery, pregnancy-induced hypertension) and pregnancy outcomes (live birth rate, clinical pregnancy rate, implantation rate). PCOS effects were summarized by adjusted odds ratios (aORs) with 95% confidence intervals (CIs) after controlling for maternal characteristics. Results: After adjusting for differences in maternal age, BMI, infertility duration, total dose of gonadotropin, serum E2 and endometrial thickness on the day of hCG trigger, number of fertilized occytes, number of embryos transferred, embryo type (cleavage-stage embryo or blastocyst) and quality, women with PCOS had an increased risk of developing unfavorable pregnancy complications, including miscarriage (aOR 1.629, 95% CI 1.240-2.141), very preterm delivery (< 32 weeks) (aOR 2.072, 95% CI 1.133-3.791). For pregnancy outcomes, PCOS was associated with higher clinical pregnancy rate (aOR 1.248, 95% CI 1.038-1.501) and implantation rate (aOR 1.238, 95% CI 1.030-1.489) after adjusting for the above-mentioned confounders. Conclusions: Women with PCOS are at increased risk of adverse pregnancy outcomes after adjusting for differences in maternal characteristics. These women may need more frequent medical consultants and management during pregnancy and parturition.